210 Pb dating of the Miaoergou ice core from the eastern Tien Shan, China. Issue 66 (2014) - Wang, Chaomin; Hou, Shugui; Pang, Hongxi; Liu, Yaping; Gäggeler, Heinz W.; Tobler, Leonhard; Szidat, Sönke; Vogel, Edith
Abstract: In 2005, two ice cores with lengths of 58.7 and 57.6 m respectively to bedrock were recovered from the Miaoergou flat-topped glacier (43°03′19″ N, 94°19′21″ E; 4512 m a.s.l.), eastern Tien Shan. 210 Pb dating of one of the ice cores (57.6 m) was performed, and an age of AD 1851 ± 6 at a depth of 35.2 mw.e. was determined. For the period AD 1851-2005, a mean annual net accumulation of 229 ± 7 mm w.e. a– 1 was calculated. At the nearby oasis city of Hami (~80 km from the Miaoergou flat-topped glacier) the annual precipitation rate is 38 mm w.e. a– 1, hence glacial meltwater is a major water supply for local residents. The surface activity concentration of 210 Pbex was found to be ~400 mBq kg– 1, which is higher than observed at other continental sites such as Belukha, Russia, and Tsambagarav, Mongolia, which have surface activity concentrations of 280 mBq kg– 1 . The 210 Pb dating agrees well with the chronological sequence deduced from the annual-layer counting resulting from the seasonalities of d 18 O and trace metals for the period AD 1953-2005, and ^ -activity horizons resulting from atmospheric nuclear testing during the period AD 1962-63. We conclude that 210 Pb analysis is a suitable method for obtaining a continuous dating of the Miaoergou ice core for ~160 years, which can also be applied to other ice cores recovered from the mountains of western China.